Evaluation of the Efficiency of the Isolated Fungi from Some Insect Species on White Fly Larvae: Bemisia Tabaci (Hemiptera: Aleyrodidae) - H.D. Abdal-Jabar (Journal of Global Pharma Technology, 2020)
The study was carried out inorder to isolation and identification of fungi associated with Formicidae pp, Pyrrhocois apterus and Coccenilla septempunctata L. and evaluate of the pathogenic ability of fungi isolated from adult bodies. Isolated fungi represented by Penicillium compactum, Penicillium janczwskii, Aspergillus terreus, Alternar of black adult ants, while the fungi were isolated penicillium chrysogenum, Beauveria bassiana, Aspergillus parasticus, Aspergillus campestris. From firebug insect, the fungi were isolated Alternaria chlamydospora, Aspergllus niger, Penicillium compactum, Ulocladium atrum of beetle insect. The results showed that the highest incidence was for fungi. Aspergllus niger and Penicillium janczwskii with equal percentage % 24.6, while the lowest incidence was for the two Aspergillus terreus Ulocladium atrum 1.5, 3.07 Respectively. The results indicated the superiority of the fungus Alternaria chlamydospora Aspergillus terreus to the rest of fungi in attracting adults Bemisia tabaci with the highest rate of affint for adults 48.0, 49.0 respectively while the lowest rate of attraction was treated with fungi Penicillium janczwskii was 0.3 adult. After five minutes later. The results clear that the highest mortality percentage of white fly was killed in the treatment of fungi Aspergillus parasticus and Ulocladium atrum the transaction amounted to% 57.17, 58.32 Respectively, while the lowest mortality percentage in the treatment of fungi Aspergillus sterreus amounted to% 38.92, It was found that the mortality percentage increased with increasing exposure time as it reached after passing 48, 70, 96,120 hours of treatment. Keywords: Isolation, Biological control, Diagnosis, Effect, Fungi, White fly, Mortality percentage.